PENGEMBANGAN BAHAN AJAR IPAS BERBASIS PENDEKATAN CRT PADA MATERI KERAGAMAN BUDAYA DI KELAS IV SD - Dinda Absi Harahap; Nurmairina; M. Faisal Husna; Dalimawaty Kadir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop digital science teaching materials based on the Culturally Responsive Teaching (CRT) approach for the cultural diversity material for fourth grade elementary school students in the form of traditional food in North Sumatra that is valid and effective for use in learning. The type of research used is Research and Development (R&D) with the ADDIE model consisting of analysis, design, development, implementation, and evaluation stages. The research subjects consisted of validators, expert questionnaire instruments, material experts, language experts, digital experts, class teachers, and fourth grade students of Lubuk Pakam National Private Elementary School. Data collection techniques used observation, interviews, questionnaire validation, and student response questionnaires. The results of the study showed that the digital teaching materials based on the CRT approach obtained a very valid category based on the assessment of expert questionnaire instruments, material experts, language experts, and digital experts. Student responses showed a very good category so that the teaching materials were declared effective for use in science learning on the cultural diversity of traditional food in North Sumatra. Thus, the digital science teaching materials based on the CRT approach are suitable for use to improve students' understanding of North Sumatran culture in fourth grade at Lubuk Pakam National Private Elementary School.